Evaluation of the use of hormonal contraceptive methods and awareness of a group of women with cardiological symptoms and diseases: Hormonal contraceptive use by women with cardiological issues - Tosun, Hülya; Ayvaz , Meryem Yıldız (Journal of Surgery and Medicine, 2024)
Background/Aim: Hormonal contraceptives can carry risks, particularly for women with chronic conditions such as heart disease and diabetes. A wide range of basic science, animal, and human studies indicate an enduringly heightened risk of venous thromboembolism, hypertension, myocardial infarction, and ischemic stroke associated with birth control hormones (estrogen and progestogen). According to the guidelines, women aged 35 and over considering hormonal contraceptives should be evaluated for vascular diseases and cardiovascular risk factors. However, the number of studies on this subject is insufficient. This study aimed to assess the use of hormonal contraceptive methods and the knowledge levels of women with cardiological symptoms and diseases attending a cardiology outpatient clinic. Methods: A descriptive and cross-sectional study was conducted with cardiological problems (diagnosed or being treated at the Cardiology Polyclinic) of women between the ages of 18 and 45. Data were collected through face-to-face interviews using the Sociodemographic Characteristics Form and the Structured Contraception Knowledge Level Form. The study sample consisted of 190 women visiting a state hospital’s Cardiology Polyclinic in Istanbul between October 2019 and January 2020. Results: Among the participants, 24.8% used hormonal contraceptives, and 15.8% reported facing problems while using them, most commonly experiencing constant headaches (53.3%) and iron deficiency (30%). The study revealed that 7.9% of the participants had cardiovascular disease, with 52.1% experiencing cardiological symptoms, such as palpitations and rapid heartbeat. A total of 24.7% had received family planning counseling, and 59.6% believed that counseling influenced their contraceptive choices. Those who received counseling showed greater knowledge regarding the safety of progesterone-only birth control pills for women with heart disease. Conclusion: Women with cardiovascular disease should be well informed about the risks associated with hormonal contraceptives. The study emphasizes the importance of counseling services provided by nurses in cardiology and obstetrics clinics to guide women toward safer contraceptive options. Continuous monitoring and education are essential to ensure women’s health and safety in contraceptive choices.